Extruded sorghum and soybeans for nursery pigs - Richert, B.T.; Hines, Robert H.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two experiments were conducted to determine the effects of extruding sorghum and soybeans for weanling pigs. The first experiment involved 66 piglets with an average age of 19 d and average weight of 10.8 lb. Two diets were fed in meal form. Treatment 1 was ground sorghum mixed with extruded soybeans, and Treatment 2 was prepared by extruding the mixture of ground sorghum and extruded soybeans. Extrusion of the sorghum-soybeans mixture increased average daily gain (ADG) and improved feed/gain (F/G) for d 0 to 14 and overall (d o to 28) compared to the ground sorghum treatment. In Exp. 2, 48 piglets averaging 23 d of age and average weight 13.0 lb were used to determine the potential for increased pig performance by double extrusion of soybeans. Diets were similar to those used in Exp. 1, with treatments of 1) ground sorghum- extruded soybeans, 2) extruded mixture of ground sorghum and extruded soybeans, and 3) ground sorghum with double-extruded soybeans. The extruded sorghum-soybeans mixture and double-extruded soybeans did not affect ADG from d 0 to 14, although there was a numerical improvement in F/G compared to the ground sorghum-extruded soybeans treatment. For d 14 to 28 and overall (d 0 to 28), average daily feed intake was reduced by extrusion of the sorghumextruded soybeans mixture and double-extruded soybeans, with no effect on ADG or F/G. Extrusion of sorghum improved growth performance of nursery-age pigs, but more information is needed to define the processing conditions and end-product characteristics that yield consistent improvements in nutritional value.
Keywords: Swine; Sorghum; Soybeans; Extrusion; Processing; Nursery